If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 4y + -2y + 4 = 0 Reorder the terms: -7 + 4 + 4y + -2y = 0 Combine like terms: -7 + 4 = -3 -3 + 4y + -2y = 0 Combine like terms: 4y + -2y = 2y -3 + 2y = 0 Solving -3 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 0 + 3 2y = 0 + 3 Combine like terms: 0 + 3 = 3 2y = 3 Divide each side by '2'. y = 1.5 Simplifying y = 1.5
| 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p | | y=kx+5 | | F(x)=15x-8 | | 5(5x-4)+11=-3 | | 7-3m=40 | | c+14c+11=7c-13 | | -2(0)+1=5-2(0) | | 2m-8=19-m | | 2(3d+c)-(4d+2c)= | | -2f=2+1-2f | | 7-3(m)=40 | | -3w+3=3-3w | | f(y)=x^2+3.6x-0.7 | | -6r-1=-2-6r | | -7q-10=-4q+8 | | 3s-10=-10+3s | | -8z=-8z-4 | | 7(2y+3)=140 | | -(0)+4=y | | 7x^2+3=-76 | | g-9=-9+g |